2013
DOI: 10.1074/jbc.m113.456764
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Screening on the Three-dimensional Model of the Plasmodium vivax SUB1 Protease Leads to the Validation of a Novel Anti-parasite Compound

Abstract: Background:The Plasmodium SUB1 protease is essential for erythrocyte egress and invasion of malaria parasites and is an attractive drug target. Results:In silico screening on three-dimensional models selected a P. vivax SUB1-competitive inhibitor, active against P. falciparum and P. berghei. Conclusion: Combined virtual screening and biological validation identified a promising hit. Significance: Targeting SUB1 could lead to a globally active antimalarial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 54 publications
1
63
0
Order By: Relevance
“…138 140 150 160 170 180 190 200 210 220 230 240 250 260 270 ARTICLE segment is not an integral part of the mature catalytic domain: (i) the multiple alignment of Plasmodium SUB1 sequences (Fig. 1b) highlights the low complexity and high variability of this segment in different species; (ii) secondary maturation sites have been identified in this region for both P. vivax and P. falciparum 21,30 (Fig. 1b); and (iii) the PvSUB1 catalytic core (as seen in the crystal composed of residues 277-611) displays the same overall architecture as bacterial subtilisin catalytic domains (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…138 140 150 160 170 180 190 200 210 220 230 240 250 260 270 ARTICLE segment is not an integral part of the mature catalytic domain: (i) the multiple alignment of Plasmodium SUB1 sequences (Fig. 1b) highlights the low complexity and high variability of this segment in different species; (ii) secondary maturation sites have been identified in this region for both P. vivax and P. falciparum 21,30 (Fig. 1b); and (iii) the PvSUB1 catalytic core (as seen in the crystal composed of residues 277-611) displays the same overall architecture as bacterial subtilisin catalytic domains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a). Inspection of the active site revealed that PvSUB1 had undergone autocleavage at its conserved primary maturation site 21 (Asp202, Fig. 1b), although the cleaved prodomain remains tightly associated to the catalytic core in the crystal.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations